2022
DOI: 10.1523/jneurosci.1661-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Signature and Target Specificity of Inhibitory Circuits Formed by Martinotti Cells in the Mouse Barrel Cortex

Abstract: We thank the ICM technical facilities PHENO-ICMICE, iGENSEQ and ICM.Quant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 84 publications
0
9
1
Order By: Relevance
“…Namely, VIP-INs showed approximately two-fold stronger tonic inhibition than SST-INs. Surprisingly, tonic inhibition in SST-INs was comparable to Pyr cells in contrast to previous study, where a weak or no tonic inhibition in SST-INs has been found ( Vardya et al, 2008 ; Donato et al, 2023 ).…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Namely, VIP-INs showed approximately two-fold stronger tonic inhibition than SST-INs. Surprisingly, tonic inhibition in SST-INs was comparable to Pyr cells in contrast to previous study, where a weak or no tonic inhibition in SST-INs has been found ( Vardya et al, 2008 ; Donato et al, 2023 ).…”
Section: Discussioncontrasting
confidence: 76%
“…Previous studies have shown no tonic inhibition in L2/3 SST-INs in the mouse frontoparietal cortex ( Vardya et al, 2008 ) and a weak tonic inhibition in L2/3 SST-INs in the barrel cortex ( Donato et al, 2023 ). However, in these studies, transgenic “GIN” mice or X98 mouse line that express enhanced green florescent protein in a subset of SST-INs were used ( Oliva et al, 2000 ).…”
Section: Introductionmentioning
confidence: 94%
“…We constrained the models with the effect of 3 μM of the α5-PAM compound, G-II-73, which was in the previously demonstrated range for selectively targeting α5 subunit receptors compared to higher concentrations that more strongly target α1, α2, and α3 subunits (Bernardo et al 2022; Prevot et al 2019). We assumed that the α5-PAM effect on tonic inhibition conductance, which we estimated from the human neuronal recordings, would also occur with synaptic conductance of SST→Pyr connections because of the localization of α5 subunits in those synapses (Ali and Thomson 2008; Davenport et al 2021; Donato et al 2023; Schulz et al 2018). The proportion of α5-PAM effects on synaptic or tonic inhibition would depend on trafficking of α5 subunits to extrasynaptic and synaptic locations, which is highly dynamic and activity-dependent (Davenport et al 2021; Jacob 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, cortical SST interneurons mediate lateral inhibition through inhibitory disynaptic loops (Obermayer et al 2018; Silberberg and Markram 2007) and provide a “blanket of inhibition” that maintains low Pyr neuron spike rates at baseline (Gentet et al 2012; Karnani et al 2016; Karnani, Agetsuma, and Yuste 2014). SST interneurons primarily target the apical dendrites of pyramidal (Pyr) neurons, where they provide both synaptic and extrasynaptic (i.e., tonic) inhibition via the α5 subunit of GABA A (α5-GABA A ) receptors (Ali and Thomson 2008; Davenport et al 2021; Donato et al 2023; Schulz et al 2018). While mostly studied in rodents, studies showed that α5-GABA A is similarly expressed in human cortical pyramidal neurons and negligibly in interneurons (Hu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation